MORREY SPACES WITH NON-DOUBLING MEASURES II - Yoshihiro Sawano (IndoMS, 2008)
The aim of this article is a survey of the research of Morrey spaces with non-doubling measures. This article is based on the lecture delivered in Institute Technology Bandung. The first half of this survey contains key results with proofs, which was written is a self-contained manner except Section 6. The second half, Parts 2 and 3, is devoted to formulating key results without proofs.DOI : http://dx.doi.org/10.22342/jims.14.2.56.121-152